(untitled) (Journal of Surgical Sciences, 2019)
Background: Breast cancer is one of the most common cancers in Bangladeshi women. Breast sacrificing treatment is still now the common practice in our country. Now a day’s breast conservative treatment is the standard treatment of breast cancer without compromising the survival. Objective: To observe local recurrence and distant metastasis free survival and overall survival of patients with breast cancer. Methods: Between January 1996 and December 2010, breast conserving treatment was carried out in 237 female patients with breast cancer in different Institutions of Bangladesh. Clinical staging was recorded by physical examination, relevant investigations as well as surgical records. Revised breast conserving surgery was carried out in those who had positive surgical margins or palpable disease. The patients with large but operable cancer or locally advanced cancer were treated by neoadjuvant chemotherapy followed by breast conserving surgery. Systemic adjuvant therapy (chemotherapy and or hormone therapy) and adjuvant radiotherapy were given in all patients. After completion of treatment, the patients were followed up with a standard protocol and data were compiled and analysed. Results: Among 237 patients who underwent breast conserving therapy 13 patients were excluded from the study for various reasons. Total 224 female patients with breast cancer who followed all the treatment schedules and attended for regular follow up were included in the study. They were between 22- 74 years of age, mean age 42.35 years; premenopausal 152 (68%). Sixty five percent (146 patients) was localized cancer (T1-2N0M0), 31.6% was regional cancer (T1-3N1M0), five cases were locally advanced stage (T4bN12M0) and two metastastatic cancer (T2-3N1M1). All most all (98%) were Infiltrating duct cell carcinoma except four which were Intraductal carcinoma in situ (IDIS). Estrogen and progesterone receptors were positive in 57% , HER2 positive (+++) in 24% of Patients. Lumpectomy/quandrentectomy with/without axillary clearance was done in 158 patients, revised breast conserving surgery in 53 cases, mastectomy in 8 cases and only biopsy done but no surgical treatment in five cases.Chemotherapy was given in 192 patients (86%); adjuvant 122 cases and neoadjuvant 70 cases. Hormone therapy in 182 patients. Radiotherapy: in 222 cases. Follow up period was 4 years to 19 years, median 10 years. Overall survival (OS) and disease free survival (DFS) was 84% and 70% respectively. Local recurrence occurred in 14(6%) cases and distant metastasis in 54 cases (24%). Conclusion: Breast conserving treatment was satisfactory for appropriate case selection and optimized therapy. Survival was no way worse than breast sacrificing treatment. Journal of Surgical Sciences (2015) Vol. 19 (2) : 55-60